THE INFLUENCE OF LEARNING VIDEO ON STUDENTS' UNDERSTANDING OF SHORT-DISTANCE RUNNING MATERIAL - Jefri, Muhammad; Rakhman, Arie; Rahmadi, Rahmadi (IKIP PGRI Pontianak, 2025)
This study aims to explore the influence of using audiovisual media in the form of learning video on students' understanding of short-distance running material in Grade VIII at SMP Negeri 1 Banjarbaru. This study employs a quantitative approach with a one-group pretest-posttest design, involving 33 students as the sample selected through purposive sampling technique. The research instruments consisted of tests (pretest and posttest), observation, and documentation, and were analyzed using normality tests, t-tests, and descriptive statistical analysis with the assistance of SPSS. The results of the study showed a significant increase in the students' average scores from 48.03 to 71.59, with an N-Gain value of 46% (moderate category). This improvement covers four indicators of understanding: (1) comprehension of basic short-distance running techniques, (2) physical benefits of short-distance running activities, (3) the role of leg muscle strength in enhancing running performance, and (4) training programs to improve students’ running performance. The paired sample t-test showed a significance value of 0.000 (< 0.05), indicating a significant influence of using learning video on improving students’ understanding. Therefore, learning video are recommended as an effective alternative medium to enhance the quality of physical education learning, particularly in short-distance running material.